Role of the suppressor of cytokine signaling-3 in the pathogenesis of Graves’ orbitopathy - Kim, Wonjin; Seo, Mi-Kyoung; Kim, Yong Joon; Choi, Soo Hyun; Ku, Cheol Ryong; Kim, Sangwoo; Lee, Eun Jig; Yoon, Jin Sook (Frontiers in Endocrinology, 2025)
ObjectiveGraves’ orbitopathy (GO) is characterized by increased production of proinflammatory cytokines and hyaluronic acid by fibroblasts and their differentiation into adipocytes in response to immunologic stimuli. The suppressor of cytokine signaling-3 (SOCS3) is an inducible negative regulator of the JAK/STAT pathway, implicated in various inflammatory diseases. In this study, we investigated the role of SOCS3 in the inflammatory and adipogenic pathogenesis of GO.MethodsTranscriptome profiling of orbital tissues obtained from five patients with GO who underwent orbital decompression surgery and four healthy subjects was performed using RNA-sequencing. Among the top-ranked differentially expressed genes, we identified 24 hub genes and found SOCS3 to be the most significantly upregulated gene in GO samples compared with that in healthy tissue based on quantitative real-time polymerase chain reaction. SOCS3 expression was analyzed in IL-1β-, and IGF-1-stimulated orbital fibroblasts using quantitative real-time polymerase chain reaction and western blot analysis. Knockdown of SOCS3 using siRNA transfection was performed to assess the effect of SOCS3 on the production of proinflammatory cytokines and adipogenic phenotype.ResultsWe identified 184 consistently differentially expressed genes—120 upregulated and 64 downregulated— in GO tissues compared to the control. SOCS3 mRNA expression was significantly higher in GO tissues (n = 17) compared with that in control (n = 15). IL-1β and IGF-1 enhanced the expression of SOCS3 at mRNA and protein levels. Silencing of SOCS3 suppressed the levels of IL-1β-induced proinflammatory cytokines, including IL-6, IL-8, and ICAM-1. Phosphorylation of NF-kB and Akt was suppressed and adipogenic differentiation was significantly attenuated by SOCS3 knockdown.ConclusionsSOCS3 was remarkably expressed in the adipose tissues of patients with GO and was induced by IL-1β and IGF-1 in orbital fibroblasts. SOCS3 inhibition attenuated the production of proinflammatory cytokines and adipogenesis, suggesting that SOCS3 may be a therapeutic target for controlling the inflammatory and adipogenic mechanisms in GO.